Students’ Perception on the Application of Gamification in Education during Covid-19 Pandemic - Noorhidayah, Sunarti; Nik Fatma Arisya, Nik Yahya; Lew, Bernard, Lew Chun Liang; Mazura, Mahdzir (INTI International University, 2022)
Covid – 19 Pandemic that hit the world had given a huge impact on all sectors of the economy including the education sector. As coronavirus continues to spread, many countries have a total lockdown. The same goes for Malaysia which the education sector needs to be closed due to Movement Control Order (MCO) 1.0, March 2020. Challenges are faced by educators as they have to conduct classes online. To gain student willingness and interest in the lesson becomes a major problem that needs attention to enhance students’ learning experience. Many educators especially in higher learning institutions using gamification apps as a method of teaching to approach and increase students’ motivation and engagement in the online classroom. Gamification refers to the application of game elements to non-gaming activities and has been applied to a variety of environments, including education. It brings a positive impact in terms of students’ behavior and academic performance. This paper aims to investigate the students’ perception of the application of gamification during the current pandemic situation. The advantages of gamification and tools to conduct gamification i.e. Kahoot, Gamified teamwork learning, and Scoreboard System have also been identified in this paper. To achieve the aim of this study, an online survey was conducted by distributing the questionnaire to the students from five selected local private universities. The data has been analyzed using descriptive statistical analysis data. The majority of the respondents agreed that gamification provides a better learning environment, increased motivation, increased understanding and memory, promotes well-being, and increased their academic performance in their learning process. The results from the survey conducted proved that these students hold a positive perception i.e. it is important to be applied in the learning process as it is being easy to use, fun, motivated, and more effective. They also feel that the lecturers shall apply gamification in the lesson.